Proteins associated with cork formation in Quercus suber L. stem tissues. - Ricardo, Cândido P P; Martins, Isabel; Francisco, Rita; Sergeant, Kjell; Pinheiro, Carla; Campos, Alexandre; Renaut, Jenny; Fevereiro, Pedro (Journal of proteomics, 2011)
Cork (phellem) formation in Quercus suber stem was studied by proteomic analysis of young shoots of increasing age (Y0, Y1 and Y4) and recently-formed phellem (Y8Ph) and xylem (Y8X) from an 8-year-old branch. In this study 99 proteins were identified, 45 excised from Y8X and 54 from Y8Ph. These ones, specifically associated with phellem, are of "carbohydrate metabolism" (28%), "defence" (22%), "protein folding, stability and degradation" (19%), "regulation/signalling" (11%), "secondary metabolism" (9%), "energy metabolism" (6%), and "membrane transport" (2%). The identification in phellem of galactosidases, xylosidases, apiose/xylose synthase, laccases and diphenol oxidases suggests intense cell wall reorganization, possibly with participation of hemicellulose/pectin biosynthesis and phenol oxidation. The identification of proteasome subunits, heat shock proteins, cyclophylin, subtilisin-like proteases, 14-3-3 proteins, Rab2 protein and enzymes interacting with nucleosides/nucleic acids gives additional evidence for cellular reorganization, involving cellular secretion, protein turnover regulation and active control processes. The high involvement in phellem of defence proteins (thioredoxin-dependent peroxidase, glutathione-S-transferase, SGT1 protein, cystatin, and chitinases) suggests a strong need for cell protection from the intense stressful events occurring in active phellem, namely, desiccation, pests/disease protection, detoxification and cell death. Identically, highly enhanced defence functions were previously reported for potato periderm formation.
Keywords: Cork; Phellem formation; Proteomics; Quercus suber stem; Suberisation

Proteomics research on forest trees, the most recalcitrant and orphan plant species. - Abril, Nieves; Gion, Jean-Marc; Kerner, René; Müller-Starck, Gerhard; Cerrillo, Rafael M. Navarro; Plomion, Christophe; Renaut, Jenny; Valledor, Luis; Jorrin-Novo, Jesús V. (Phytochemistry, 2011)
The contribution of proteomics to the knowledge of forest tree (the most recalcitrant and almost forgotten plant species) biology is being reviewed and discussed, based on the author's own research work and papers published up to November 2010. This review is organized in four introductory sections starting with the definition of forest trees (1), the description of the environmental and economic importance (2) and its derived current priorities and research lines for breeding and conservation (3) including forest tree genomics (4). These precede the main body of this review: a general overview to proteomics (5) for introducing the forest tree proteomics section (6). Proteomics, defined as scientific discipline or experimental approach, it will be discussed both from a conceptual and methodological point of view, commenting on realities, challenges and limitations. Proteomics research in woody plants is limited to a reduced number of genera, including Pinus, Picea, Populus, Eucalyptus, and Fagus, mainly using first-generation approaches, e.g., those based on two-dimensional electrophoresis coupled to mass spectrometry. This area joins the own limitations of the technique and the difficulty and recalcitrance of the plant species as an experimental system. Furthermore, it contributes to a deeper knowledge of some biological processes, namely growth, development, organogenesis, and responses to stresses, as it is also used in the characterization and cataloguing of natural populations and biodiversity (proteotyping) and in assisting breeding programmes.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21353265
Keywords: Forest tree proteomics; forest trees; Plant proteomics; Woody plants